Serum Clusterin Level Could Reflect the Current Activity of Antineutrophil Cytoplasmic Antibody-Associated Vasculitis - Yoon, Taejun; Ahn, Sung Soo; Pyo, Jung Yoon; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won (Yonsei medical journal, 2021)
We investigated whether serum clusterin levels could reflect the current antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV)-specific indices. Fifty-seven patients with AAV and 40 healthy controls were included in this study. AAV-specific indices included the Short-Form 36-Item Health Survey Physical and Mental Component Summaries (SF-36 PCS and MCS) scores, Birmingham vasculitis activity score (BVAS), five-factor score (FFS), and vasculitis damage index. Clinical and laboratory data and AAV-specific indices were obtained at blood collection. The highest tertile of BVAS (≥16) was defined as high activity of AAV. The median age of AAV patients was 64.0 years and 19 patients were male. SF-36 PCS score (r=0.328), SF-36 MCS score (r=0.289), BVAS (r=-0.404), erythrocyte sedimentation rate (r=-0.336), and C-reactive protein levels (r=-0.421) were significantly correlated with serum clusterin levels. In the multivariable linear regression analysis using AAV-specific indices and serum clusterin levels, both FFS (β=0.412) and serum clusterin levels (β=-0.250) were significantly associated with BVAS. When the optimal serum clusterin cut-off level for high activity of AAV was identified as 130.45 µg/mL, patients with serum clusterin level ≤130.45 µg/mL had a significantly higher risk for high activity of AAV than did those without (relative risk 7.194). Patients with AAV exhibited significantly lower serum clusterin levels than did healthy controls (168.2 µg/mL vs. 230.5 µg/mL). Serum clusterin levels could reflect the current disease activity in patients with AAV.